Association between oral health literacy and oral health-related quality of life among undergraduate students in Bengaluru city - Gaurav Sharma; Manjunath P Puranik; K R Sowmya (Wolters Kluwer Medknow Publications, 2014)
Introduction: Oral health literacy (OHL) is the new imperative for better oral health as health literacy is now considered a determinant of health. The complexity of both verbal and written oral health communications creates a significant barrier to improving oral health. Aim of the Study: To determine the association between OHL and oral health-related quality of life (OHRQoL) among undergraduate students in Bengaluru City. Materials and Methods: For a cross-sectional survey among 400 undergraduate students (PUC, BA, B.Com, BBM, B.Sc, BE), 10 colleges were randomly selected in Bengaluru city. The structured proforma including oral health impact profile-14 (OHIP-14) was administered to the study participants. Rapid estimate of adult literacy in dentistry-30 (REALD-30) was provided to each participant to be read aloud in front of the interviewer. The data were analyzed using descriptive statistics, ANOVA and correlation coefficient test. A P < 0.05 was considered to be significant. Results: Mean OHIP-14 score ranged from 16.2 ± 3.52 (BBM) to 21.5 ± 7.5 (BA) with significant differences among streams (P = 0.036). Mean REALD-30 ranged from 12.76 ± 4.61 to 18.85 ± 3.42 with significant differences between groups (P < 0.001). OHIP-14 and REALD-30 showed positive correlation for PUC (r = 0.072), B.Com (r = 0.314), B.Sc (r = 0.448) and BE (r = 0.245); negative correlation for BBM (r = −0.09). However significant correlation was observed among B.Sc and BE students (P < 0.05). Conclusion: Oral health literacy was significantly associated with OHRQoL. Hence raising OHL levels may have an impact on OHRQoL.